(Re)discovering Pedagogy of the Oppressed (LEARNing Landscapes, 2021)
This article chronicles a crisis of alignment regarding Critical Pedagogy due to the top-down power structures of White authority that is pervasive in the theory’s North American academic environment. Contesting the often touted “radical” or “revolutionary” nature of Critical Pedagogy in higher education spaces, the author questions his relationship with Paulo Freire’s work, Pedagogy of the Oppressed, ultimately abandoning the content of writing over the way the theory/philosophy is lived in academia. Through the lived experience of engaging with community in the James Bay Cree territories and Malawi, the question is asked as to who owns Freire’s rebellious call to action.
Keywords: Paulo Freire; critical pedagogy; racism; White privilege; praxis